ISLAMIC BANKING STUDENTS' NEEDS FOR EAP ONLINE LEARNING IN INDONESIA - Ratna Yunita (Universitas Muhammadiyah Makassar, 2022)
This study aimed at investigating Islamic Banking students' needs for English for Academic Purposes (EAP) online learning in Indonesia. This research method was a descriptive survey expecting to discover the target and learning needs related to online learning. This study used a questionnaire distributed three distinctive times to 572 students of the Islamic Banking department at the State Institute for Islamic Studies (IAIN) of Ponorogo from 2020 to 2021. The observation was also used to support the data. The results discovered students' preference on the platforms used to support online learning, whether it was a virtual tool to replace in-person teaching or the learning management system, the effective duration of virtual meetings, language used and learning activities in the teaching and learning process. The reasons for students’ preferences and some students' inputs to the EAP online learning were also revealed. The needs analysis research may provide a basis for innovative online EAP course design and help prepare and deliver EAP online learning.